Hepatitis C Virus Induced a Novel Apoptosis-Like Death of Pancreatic Beta Cells through a Caspase 3-Dependent Pathway - Wang, Qian; Chen, Jizheng; Wang, Yun; Han, Xiao; Chen, Xinwen (PLOS ONE, 2012)
Epidemiological and experimental studies have suggested that Hepatitis C virus (HCV) infection is associated with the development of type 2 diabetes. Pancreatic beta cell failure is central to the progression of type 2 diabetes. Using virus infection system, we investigate the influence of HCV infection on the fate of the insulinoma cell line, MIN6. Our experiments demonstrate that the HCV virion itself is indispensable and has a dose- and time-dependent cytopathic effect on the cells. HCV infection inhibits cell proliferation and induces death of MIN6 cells with apoptotic characteristics, including cell surface exposure of phosphatidylserine, decreased mitochondrial membrane potential, activation of caspase 3 and poly (ADP-ribose) polymerase, and DNA fragmentation in the nucleus. However, the fact that HCV-infected cells exhibit a dilated, low-density nucleus with intact plasma and nuclear membrane indicates that a novel apoptosis-like death occurs. HCV infection also causes endoplasmic reticulum (ER) stress. Further, HCV RNA replication was detected in MIN6 cells, although the infection efficiency is very low and no progeny virus particle generates. Taken together, our data suggest that HCV infection induces death of pancreatic beta cells through an ER stress-involved, caspase 3-dependent, special pathway.